PRE-OPERATIVE ANEMIA AS A PREDICTIVE MORBIDITY OUTCOME — A RETROSPECTIVE ANALYSIS OF A VASCULAR SURGERY DEPARTMENT - Semião, Carolina (2020)
Introduction: Anemia is associated with increased adverse outcomes during the early postoperative period because of high physiologic stress and increased cardiac demand. The aim of this study was to assess the relationship between pre-operative anemia and morbi-mortality outcomes in patients undergoing elective carotid endarterectomy (CEA), open aortic repair (OAR) or endovascular aneurysm repair (EVAR) of abdominal aortic aneurysms (AAA) and infrainguinal bypass surgery in chronic limb-threatening ischemia.  Methods: Retrospective analysis of all elective patients between 2016-2018, who underwent: CEA, OAR, EVAR and infrainguinal bypass surgery in chronic limb-threatening ischemia. Emergency procedures and transfusion of more than 4 units of red blood cells (RBC) were excluded. Hemoglobin levels were categorized according to the WHO definition for anemia: severe (< 8 g/dL), moderate (8-10.9 g/dL), mild (11-11.9 g/dL in women and 11-12.9 g/dL in men) and no anemia (≥12 g/dL in women and ≥13 g/dL in men).  Results: Our study population comprised 257 patients, of which 74 (28%) underwent EVAR, 26 (10.1%) OAR, 67 (26.1%) CEA and 90 (35%) infrainguinal bypass. Pre-operative anemia was identified in 37.4% (n = 96) of the patients. Of those, 67.7% (n = 65) had mild anemia and 32.3% (n = 31) had moderate-severe anemia. Anemic patients have longer length of stay when compared with non-anemic patients (16.61±16.5; 7.68±4.92, respectively) (p = 0.022) and also longer stay in the post-operative care unite in comparison with patients with hemoglobin within the normal range (average 2.08 days ± 1.12; 1.77 days ± 1.01, respectively) (p<0.001). Pre-operative anemia was associated with the need of peri-operative transfusions (p < 0.001), as expected. In-hospital adverse events were influenced by the presence of anemia (p<0.001), namely surgical site infection (p = 0.002) and re-intervention (p<0.007). Patients who received blood transfusion peri-operatively were more prone to adverse outcomes (p<0.001), such as renal disfunction (p = 0.006), respiratory infections (p =0.015), surgical site infection (p = 0.001) and re-intervention (p = 0.001).  Conclusion: Pre-operative anemia evaluation should be incorporated into the preoperative risk assessment. Iron deficiency anemia is the most frequent type of anemia. In these cases, oral or IV iron supplementation pre-operatively is the preferential treatment, and might decrease the need of blood transfusions. Patients with iron deficiency without anemia also have indication to take oral iron supplementation. This situation urges the application of a well-structured protocol to optimize pre-operative hemoglobin, reduce intra-operative blood loss and improve anemic patients’ status in an effort to reach better outcomes.